(untitled) (Bangladesh Journal of Urology, 2020)
Vesicovaginal fistula (VVF) is one of the oldest diseases of women of child bearing age. It is more common in developing countries and has been a great social and a surgical challenge to Urologists as well as Gynecologists. Though, there have been lot of developments in the understanding the diagnosis, treatment and use of modern technologies for these fistulae but controversies still exists regarding timing and ideal approach for repair. Every woman with obstetric fistula suffers a very miserable life, either socially outcast separated or divorced, unless any help comes forward. 62 cases of fistula were operated at Kumudini Medical College Hospital, Tangail, from April 08 to May 09. Out of these, 50 (80.65%) patients have been cured. This review was taken to look into the results of operation in a peripheral private Medical College with insufficient facilities. Though, prevalence of obstetric fistula was more in our series but number of fistula cases is rising following gynecological operations. VVF is a preventable disease, so more emphasis should be given on the prevention. Surgical operation is the only treatment for VVFs and it doesn’t require too many costly instruments but experience of the surgeon is very important. The scale of problem in our country is enormous. Safe motherhood is birth right of every woman, Government & society should provide that at any cost. Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.44-47